Problems of Creation of Social Experience in Motor Games of Children Aged 5-7 Years - Serykh, L.V.; Kondakov, V.L.; Buchek, A.A.; Voloshyna, L.N.; Galimskaia, O.G. (International Journal of Criminology and Sociology, 2022)
The objective of the study is to identify the level of recreation of social experience by children of 5-7 years old in motor games. Methods: theoretical: analysis, synthesis, generalization; empirical: observation and evaluation of independent motor activity of children, game diagnostic situations, conversation; methods of mathematical statistics: Mann-Whitney U-test. Materials. The study involved 625 older preschool children (312 girls and 313 boys) attending Municipal Budgetary Pre-school Educational Institution nursery schools No. 56 and 76 in Belgorod, Municipal Autonomous Pre-school Educational Institution “Gnomik” nursery school No. 78 in Belgorod; Municipal Preschool Educational Institution nursery schools No. 3, 4, and 8 of the city of Valuyki, Belgorod region; Municipal Autonomous Pre-school Educational Institution nursery schools No.2, 32, 35, and 37 of the city of Gubkin, Municipal Budgetary Pre-school Educational Institution "Veselinka" nursery school No. 40 of the city of Gubkin, and Municipal Budgetary Pre-school Educational Institution nursery schools No. 19 and 36 of the city of Gubkin, Belgorod region. Results The relevance of the study is due to the presence of a high potential of motor games in terms of its sociological component and pedagogical determinants. The need to comprehend and implement this potential in pedagogical practice in order to positively socialize a growing person. In modern studies, motor-game activity is considered as a method of complex influence on the child, contributing to his physical, cognitive, communicative, socio-cultural development. Summary. Analysis of the results of the study showed that 78.7% of children aged 5-7 years old successfully use social experience in motor games and show an optimal and sufficient level of its reconstruction. At the same time, 1/5 of the children: - have difficulty in planning and discussing joint actions in the game, the distribution of game functions; - violate the rules of interaction during the game; - insufficiently dynamic and proactive in the development of the plot of the game; - feel difficult to determine their own playing roles, the overall assessment of the game. Significant gender differences in the reconstruction of social experience in the motor games of older preschoolers have not been found.